The patterns of presentation, management and outcomes of breast cancer patients at a tertiary health facility in Sierra Leone - Constance Cummings-John; Abdulai Jawo Bah; Isaac Olufemi Smalle; Caesar Cho Challe; Babatunde Duduyemi; Temidayo Ogundiran (BMC Cancer)
Abstract Background Breast cancer is the leading cause of cancer among women globally and the most common cancer among women in Sierra Leone. This study aimed to evaluate the patterns of clinical presentation, management and outcomes among breast cancer patients who presented at the Connaught Teaching Hospital Complex in Sierra Leone. Method A retrospective, cross-sectional study was conducted at the specialist outpatient clinic at the Connaught Hospital. The medical records of 253 breast cancer patients were selected through convenience sampling on the basis of the completeness of their data from 2018 to 2021. The patients’ sociodemographics, obstetrics-gynecological history, clinicopathological characteristics, treatment modalities, and outcomes were analysed via SPSS version 24. Results Among the 253 patients with breast cancer, 246 (97.2%) were female, and the mean age of the patients was 47 ± 14 years. The mean age at menarche was 12 ± 3 years, and 35 (13.8%) patients had a family history of breast cancer. The left breast of 130 (51.2%) patients was the most commonly affected; approximately 119 (47%) patients presented with stage III B disease, and 35 (13.8%) presented with metastasis. With respect to treatment modalities, surgery, chemotherapy, and hormonal therapy were provided to patients — with 120 (48%) mastectomies, 73 (29.2%) neoadjuvant chemotherapy, 84 (33.6%) adjuvant chemotherapy, 98 (39.2%) hormonal therapy, 35 (14.0%) palliative care and approximately 38 (15.2%) refused or did not initiate any treatment. Among the outcomes of breast cancer patients, 19 (32.8%) was the highest mortality rate in 2019, and 10 (27.8%) was the lowest in 2018. Conclusion Our study revealed that over half of our breast cancer patients presented with advanced-stage disease, and mastectomy was the most common modality of treatment. Further studies are needed to understand the factors responsible for their late presentation and improve histological services and access to radiotherapy facilities for our patients.